Analysis of Waqf Validity in the Perspective of Positive Law and Islamic Law: A Case Study of Decision No. 453/Pdt.G/2020/PA.Kdi - Paramitha, Attahiraa Prajna; Huda, Miftahul (Sakina: Journal of Family Studies, 2025)
The practice of waqf plays a significant role both as an act of worship and as a social asset supporting development. However, disputes often arise regarding the management and utilization of waqf land that do not comply with legal regulations. A case in Kadia Subdistrict, Kendari City, illustrates the legal dualism in determining the validity of waqf. This study aims to analyze judicial decisions on the validity of waqf from the perspectives of positive law and Islamic law, focusing on Decision No. 453/Pdt.G/2020/PA.Kdi. This research employs a normative legal method with a case approach, utilizing secondary data from legal regulations, court decisions, and literature on Islamic and positive law. The findings indicate that the court ruled to revoke the waqf status due to non-compliance with formal requirements under positive law, specifically the absence of an Authentic Deed of Waqf (AIW). However, from the perspective of Islamic law, the waqf remains valid as it fulfills the essential pillars of waqf. This discrepancy highlights a potential conflict between positive law and Islamic law in waqf practices in Indonesia. This study emphasizes the importance of harmonizing positive law and Islamic law in resolving waqf disputes to provide more comprehensive legal certainty. Strengthening regulations and raising awareness about proper waqf procedures under both legal systems are necessary to prevent future disputes.